2013
DOI: 10.1109/tmm.2013.2240670
|View full text |Cite
|
Sign up to set email alerts
|

CloudMoV: Cloud-Based Mobile Social TV

Abstract: Abstract-The rapidly increasing power of personal mobile devices (smartphones, tablets, etc.) is providing much richer contents and social interactions to users on the move. This trend however is throttled by the limited battery lifetime of mobile devices and unstable wireless connectivity, making the highest possible quality of service experienced by mobile users not feasible. The recent cloud computing technology, with its rich resources to compensate for the limitations of mobile devices and connections, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Then, to communicate with the main thread executing HTML5, postMessage is used to deliver a message and the delivered message is processed through the message. Moreover, as background operation is possible, many mobile resources are likely to be utilized in accompanying smartphone applications [25,26]. Web Workers make JavaScript processing effective in terms of function, but the results of the test conducted in this research revealed that the browser on a desktop PC displays lower performance due to limitations in mobile resources [27].…”
Section: Javascript Multi-threadmentioning
confidence: 87%
“…Then, to communicate with the main thread executing HTML5, postMessage is used to deliver a message and the delivered message is processed through the message. Moreover, as background operation is possible, many mobile resources are likely to be utilized in accompanying smartphone applications [25,26]. Web Workers make JavaScript processing effective in terms of function, but the results of the test conducted in this research revealed that the browser on a desktop PC displays lower performance due to limitations in mobile resources [27].…”
Section: Javascript Multi-threadmentioning
confidence: 87%
“…[20]- [22] proposed a model for cloud based video Transcoding services for mobile devices. L.Yao et al [24] measured a server side workload for mobile streaming service provision. The survey covers the Transcoding of the video contents, audio video formats, device heterogeneity and hardware, software variations and practical limitations on service provision.…”
Section: Related Workmentioning
confidence: 99%
“…It provides services on demand [9] and with great comfort [10]. Infrastructure as a service (IaaS) of cloud services can be used for storing videos on the cloud [8], [11] so that it can be accessed faster and easily. Cloud computing has number of benefits [12] for users like on demand service, pay per use, scalability and availability services.…”
Section: Literature Reviewmentioning
confidence: 99%